PENINGKATAN KETERAMPILAN BERCERITA DENGAN MENGGUNAKAN METODE STORYTELLING BERBANTUAN MEDIA GAMBAR DI SEKOLAH DASAR - Junia Dinda Putri; Iis Aprinawati; Rusdial Marta; Rizki Ananda; Yanti Yandri Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low storytelling skills of students in class III SDM 002 Penyasawan, the purpose of this research is to improve storytelling skills through storytelling methods assisted by image media. The method used is Class Action Research (CAR) which is carried out in two cycles, each cycle consists of two meetings with stages of planning, implementation, observation and reflection. The research subjects amounted to 28 students. Data collection techniques are carried out through documentation, observation, and tests. The research instrument is in the form of observation sheets of teacher and student activities as well as documentation of the learning process. Data were analyzed descriptively, qualitatively, and quantitatively through the calculation of average test scores and analysis of the development of learning activities. The results of the study showed an increase in the classical completeness of the pre-action, which was 25%, in the first cycle of the first meeting to 25%, then in the first cycle of the second meeting it increased to 53.57%. Furthermore, in the second cycle of the first meeting it was 71.42% and in the second cycle of the second meeting reached 92.85%. Based on these findings, it can be concluded that the storytelling method assisted by image media can improve the storytelling skills of students in class III 002 Penyasawan